In waves [compact disc] - Jamie xx (Young, 2024)
The long-awaited new album by Jamie xx is the next chapter in the career of one of the most in-demand producers of his generation. With this album, Jamie replicates the emotional crescendos and thrilling volatility of an almost mystical night out, one where you return home in the cigarette ash dawn, the specifics of the last eight hours already blurring, but aware that these feelings will remain a crystalline memory. It is a melancholy paradise of bliss, heartbreak, and introspection. The story of a journey where you merge into the divine pulse of shadows, light, and dancefloor rhythms. A strobe light epiphany about the illimitable possibilities and spiritual capacities of humanity.